2020
DOI: 10.1016/j.jaut.2020.102473
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognostic factors of disease severity in patients with COVID-19: The Beijing experience

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
185
5
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(226 citation statements)
references
References 25 publications
18
185
5
7
Order By: Relevance
“…In the single‐center study by Da et al in the United States, abnormalities in aminotransferase, lactate dehydrogenase (LDH), and ferritin levels were observed in five cases with COVID‐19‐related liver injury 73 . Sun et al found that serum ferritin was high in severe and critically ill groups ( P < .001), and was positively associated with alanine aminotransferase (ALT) ( r = .385, P = .002), aspartate transaminase (AST) ( r = .437, P < .001), and LDH ( r = .394, P = .001) levels, but not with alkaline phosphatase (ALP) and gamma‐glutamyl transferase (GGT) 74 . Multivariable analysis in the study by Phipps et al also revealed that severe acute liver injury was significantly associated with high levels of ferritin (OR 2.40, P < .001) and these subsets of patients had a more severe clinical course 75 .…”
Section: Resultsmentioning
confidence: 99%
“…In the single‐center study by Da et al in the United States, abnormalities in aminotransferase, lactate dehydrogenase (LDH), and ferritin levels were observed in five cases with COVID‐19‐related liver injury 73 . Sun et al found that serum ferritin was high in severe and critically ill groups ( P < .001), and was positively associated with alanine aminotransferase (ALT) ( r = .385, P = .002), aspartate transaminase (AST) ( r = .437, P < .001), and LDH ( r = .394, P = .001) levels, but not with alkaline phosphatase (ALP) and gamma‐glutamyl transferase (GGT) 74 . Multivariable analysis in the study by Phipps et al also revealed that severe acute liver injury was significantly associated with high levels of ferritin (OR 2.40, P < .001) and these subsets of patients had a more severe clinical course 75 .…”
Section: Resultsmentioning
confidence: 99%
“…CD4+ and/or CD8+ T‐cell counts from COVID‐19 patients with different disease severity status were reported in all 20 publications, and 10 of them also included CD19+ B cell and CD16 + CD56+ NK cell counts. These 20 peer‐reviewed publications were selected for meta‐analysis in this brief report (6‐25).…”
Section: Methodsmentioning
confidence: 99%
“…Most importantly no studies conducted on post recovery patients addressing those markers. In mild-moderate COVID-19 patients the in ammatory proteins that have effect on ESR boosting maintain in their minimum level, subsequently ESR stays in their normal range 41 . Our study seems to be the rst attempt to observe those biological markers in COVID-19 post recovery patients.…”
Section: Resultsmentioning
confidence: 99%